Fuzzy Based Evaluation of Digital Connectivity Across Countries Using Mamdani Fuzzy Inference System - Saragih, Asido; Jaya Santoso; Ana Muliyana (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2026)
Digital connectivity plays an important role in supporting economic growth and social inclusion. However, measuring it across countries is not straightforward because it involves several indicators and a certain level of uncertainty. In this study, we applied a Mamdani Fuzzy Inference System (FIS) to assess digital connectivity in 137 countries. The data were taken from the ITU and World Bank (2024), including Internet Users, Fixed Broadband Subscriptions, and Mobile Cellular Subscriptions. We built a rule-based system using five linguistic categories and adjusted the membership functions based on the data distribution. The centroid method was then used to generate a Digital Connectivity Index (DCI) on a scale of 0 to 100. The results indicate a clear gap in global connectivity. A total of 23 countries achieved a Very High DCI (≥ 80), mostly located in Western Europe and East Asia. In contrast, 17 countries fell into the Very Low category (< 20), mainly from Sub-Saharan Africa. The global average DCI was 53.47. Overall, the proposed approach provides a clear and easy-to-understand classification that can support policy analysis and evaluation of digital development.